Effectiveness Study of KTMB Track Inspection Methods to Improve Track Quality - Shahrizal, Shafizal Haqimi; MUHAMAD FAIZ BIN ABD LATIF,; Shaiful Amir Bin Leman, (Progress in Engineering Application and Technology, 2023)
Contactless-Laser Detection enhances railway inspection capabilities, using Track Gauge, Amber Geismar, and EM120T to monitor infrastructure condition and prevent breakdowns. However, inconsistencies in inspection results can affect maintenance decisions and decision-making. The main objective for this study is to analyze the effectiveness of track inspection method and suggestion for future improvement of track inspection method used to KTMB which will involve with analyzation data of three inspection method (Track Gauge, Amber Geismar and EM120T) at KM 421.550 to KM 421.670 (UKM to Bangi). Static track inspection data will be collected using Track Gauge to measure gauge, cant, twist, and surface. Amber Geismar can measure surface parameters, but surface parameters are unavailable. Dynamic track inspection data will be collected using EM120T machinery, creating graphs and exception reports. OIE (overall inspection effectiveness) is used for evaluation. The study demonstrates EM120T as the most efficient approach for track inspection, enabling quick assessment of seven parameters. A reliable conversion multiplier converts static data from Track Gauge and Amber Geismar. This study focuses on railway track locations, including straight lines and gradients, to determine the impact of inspection results. The multiplier may change if inspections are conducted at curves. The study used unmaintained tracks and recommended acting on inspection findings after maintenance.  The application of a multiplier to convert static and dynamic track data can be enhanced. The results may be strengthened if the obtained multipliers vary slightly, but a significant gap can make it easier for inspectors to conduct track inspections in different categories.